Development and characterization of topical analgesic ointment - from laboratory to production scale - Md Adib, Noor Adibah; Chatterjee, Bappaditya; Mandal, Uttam Kumar; Mohamed, Farahidah (2016)
The purpose of this study was to scale up an ointment formulation containing 25% w/w methyl salicylate, developed via 300-g laboratory batches to 45-kg batch sizes in a homogenize mixer. Method: The ointment was manufactured by fusion method in a homogenous mixer. Characterization was conducted for assay of ingredients by a validated GC-FID method, physicochemical properties and microbial limit test. Further, optimized formulation was scaled up at large scale. Result: The desired analgesic ointments were developed and evaluated which contains petrolatum base (30%), Beeswax 1540 (20%) , methyl salicylate (10%), Menthol crystal (5 %),Camphor powder (5 %). The drug content were within specification. The stable formulation was observed during laboratory scale as well as at production scale. Successful scale up for 45kg batches were carried out. Conclusion: A topical analgesic ointment was developed and successfully scaled up that can be commercialized after meeting relevant regulatory requirements.